Efficacy of a new treatment algorithm for capsulitis of the fingers in rock climbers - Schöffl, Volker Rainer; Lutter, Christoph; Lang, Hans Christoph; Perl, Mario; Moser, Othmar; Simon, Michael (Frontiers in Sports and Active Living, 2025)
Background: Although finger joint capsulitis has been described among the most frequent injuries in climbers, no clinical studies on treatment strategies and outcomes are available. Study design: Prospective case series study. Methods: Between 2015 and 2018 we prospectively treated 50 patients (38 male, 12 female) with a total number of 69 independent finger joint capsulitis according to a clinic specific treatment regimen and evaluated the outcome retrospectively. Therapy consisted of either conservative management, steroid injections, radiosynoviorthesis or a combination depending on the treatment regimen, prior therapy and timeline of symptoms. Outcomes were assessed using visual analogue scale (VAS), Buck-Gramcko score and a climbing specific outcome score with secondary patient recall. Results: The proximal interphalangeal joint of the middle finger was the most commonly affected joint, and there was no correlation with osteoarthritis. All climbers returned to sport within 12 months. The majority were able to maintain their level of performance after injury and the difference in climbing level before and after injury was not statistically significant (p = 0.22). The total time spent climbing was significantly less after the injury than before the injury (p < 0.001). The Buck-Gramcko score showed excellent results. The overall functional outcome was good to very good with a mean score of 1.6 ± 0.7, as was the climbing specific score of 1.7 ± 0.9. Pain was significantly less after treatment than before (p < 0.001). Conclusion: Good to very good functional and sport-specific outcomes were seen with the stage-specific treatment regimen presented, allowing all patients studied to resume climbing. A better understanding of the underlying pathogenesis is essential in order to better assess long-term progress.
CRIS-Team Scopus Importer:2025-02-14
Keywords: capsulitis; finger injuries; finger joint synovitis; rock climbing; sport climbing